S143 Serum CYFRA 21–1 as a prognostic marker in scleroderma-associated interstitial lung disease. (December 2018) - Stock, CJW; Hoyles, R; D'accord, C; Kokosi, M; Alfieri, V; Campochiaro, C; Donovan, J; Mori, L; Maher, TM; Kouranos, V; Margaritopoulos, G; George, PM; et al.
Abstract : Interstitial lung disease (ILD) is the main cause of death in systemic sclerosis (SSc). The progression of SSc associated ILD (SSc-ILD) is highly variable. Markers predictive of progressive ILD are needed early in the disease course, to appropriately target patients at risk of developing progressive pulmonary fibrosis. CYFRA 21–1 (CYFRA) is a tumour marker expressed by type I/type II pneumocytes and respiratory bronchiolar epithelial cells, released into the blood following cell lysis. Serum levels of CYFRA were measured in both a retrospective (n=180) and a prospective (n=118) cohort of SSc patients. Retrospective cohort mean age: 49.1 (range 47.08–51.05), 77.25% female, prospective cohort age: 56.4 (54.10–58.73), 76.23% female. Median FVC% predicted and DLCO% predicted: retrospective cohort: 80.1% (IQR:67.2–95.5) and 55.5% (44.3–68.35), respectively – prospective cohort: 73.8% (57.2–87) and 39.9% (29.2–48.8), respectively. ILD was defined as the presence of fibrosis on chest imaging (chest x-ray or HRCT) and/or a forced vital capacity (FVC) <75% when no CT within 2 years of serum sample collection was available. Mortality and disease progression (time to decline in pulmonary function indices) were quantified from the time of serum collection (±6 months). Cox proportional hazards analysis was used to determine the relationship between CYFRA levels and disease progression/mortality. Statistical analysis was performed using STATA12. In both cohorts, CYFRA was lowest in patients without ILD (median:1.44 (IQR:1.11–1.855) ng/ml), and highest in patients with extensive (2.68 (2.22–3.57) ng/ml), rather than limited ILD (1.8 (1.34–2.53) ng/ml, p=0.0001), according to the Goh al staging system (CT extent integrated as necessary by FVC). In the retrospective cohort, on both univariate and multivariate analyses (adjusting for severity, allele carriage, gender, age, ethnicity, and smoking history), serum CYFRA was an independent marker of survival and time to decline in FVC ≥10% and DLCO ≥15%. The association with decline in DLCO15% was replicated in the prospective cohort. Our results suggest that serum CYFRA may be an effective prognostic biomarker in SSc-ILD. This suggests that epithelial cell damage plays an important role in pathogenesis of SSc-ILD.